Curriculum Instability and the Future of Islamic Education in Indonesia: Lessons from the Decentralized Education System in the United States - Jasuli; Imron Fauzi; Ali Saeed (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This study examines curriculum instability and its implications for the future of Islamic education in Indonesia through a comparative analysis of the decentralized educational governance system in the United States. The study aims to analyze how centralized curriculum policies and repeated educational reforms affect the sustainability, adaptability, and institutional resilience of Islamic educational institutions in Indonesia. This research employed a qualitative approach using the Systematic Literature Review (SLR) method. A total of 77 scholarly references published between 2019 and 2026 were analyzed using the PRISMA framework and thematic analysis. The review focused on curriculum instability, centralized governance, Islamic educational transformation, and decentralized educational systems. The findings reveal that curriculum instability in Indonesia reflects a structural governance problem characterized by policy discontinuity, centralized decision-making, and fragmented educational implementation. These conditions create significant challenges for pesantren, madrasahs, and Islamic schools in maintaining institutional sustainability and educational identity. In contrast, the decentralized educational governance system in the United States demonstrates how institutional autonomy, adaptive policymaking, and contextual flexibility may strengthen educational resilience and curriculum sustainability. The novelty of this study lies in its integration of curriculum instability, comparative educational governance, and Islamic educational transformation within a single analytical framework. This study contributes theoretically by positioning curriculum instability as a governance-based issue affecting the future sustainability of Islamic education. Practically, the findings offer strategic insights for reconstructing adaptive, collaborative, and future-oriented Islamic educational governance in Indonesia.